2012
DOI: 10.1007/s10267-011-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Muscodor sutura, a novel endophytic fungus with volatile antibiotic activities

Abstract: Muscodor sutura is described as a novel species that is also an endophyte of Prestonia trifidi. Uniquely, this fungus produces a reddish pigment, on potato dextrose agar (PDA), when grown in the dark. In addition, the organism makes some volatile organic compounds that have not been previously reported from this genus, namely, thujopsene, chamigrene, isocaryophyllene, and butanoic acid, 2-methyl. These and other volatile compounds in the mixture possess wide-spectrum antifungal activity and no observable antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 14 publications
2
43
0
1
Order By: Relevance
“…Although there was still need to confirm this hypothesis by performing for instances bioassays, the joint action of these VOCs seems to have potential utility in the treatment of infectious diseases caused by bacteria and yeasts. In fact, VOCs extracted from endophytic fungi have been reported to have antimicrobial effects against a variety of human and plant pathogens (Kudalkar et al 2012;Mitchell et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was still need to confirm this hypothesis by performing for instances bioassays, the joint action of these VOCs seems to have potential utility in the treatment of infectious diseases caused by bacteria and yeasts. In fact, VOCs extracted from endophytic fungi have been reported to have antimicrobial effects against a variety of human and plant pathogens (Kudalkar et al 2012;Mitchell et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic fungi are one of the potential sources of novel antimicrobial compounds, due to chemical diversity of their secondary metabolites. So far, studies reported a wide range of novel antimicrobial compounds produced by endophytic fungi belonging to diverse structural classes, including alkaloids, peptides, steroids, terpenoids, phenols, phenylpropanoids, aliphatic compounds, polyketides, quinones and flavonoids (Mousa and Raizada 2013;Yu et al 2010), as well as volatile organic compounds (VOCs) such as esters, lipids, alcohols, acids, ketones, among others (Banerjee et al 2010;Kudalkar et al 2012). However, several studies have shown that the plant host, and ultimately its metabolism, influences the synthetic ability of endophytes (Strobel 2006;Ul-Hassan et al 2012), which could prevent these microorganisms from being used in a commercial production of antimicrobial compounds (Kusari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…C. lusitanica [65] Thujopsanol, thujopsene Xylaria sp. C. lusitanica [65] M. sutura P. trifidi [71] Ylangene Phoma sp. L. tridentata [66] Zingiberene Xylaria sp.…”
Section: Albusmentioning
confidence: 99%
“…(2), according to searches in UNITE database using DNA sequences of internal transcribed spacer (ITS) ( Table 1). Muscodor is a genus of sterile endophytic fungi, all species of this genus were characterized by the production of volatile organic compounds (VOCs) that inhibit the growth of other microorganisms (STROBEL et al, 2001a;STROBEL, 2006b;STROBEL, 2011c;STINSON et al, 2003;JIMENEZ, 2004;MANKER 2005;MERCIER et al, 2007;WORAPONG;STROBEL, 2009;ZHANG et al, 2010;SUWANNARACH et al, 2012;KUDALKAR et al, 2012;SAXENA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%